The patient with renal disease. Issue 8 (August 2016) - Johnson, Christopher; Gibson, Bruce
Abstract: Chronic kidney disease has a wide spectrum of multisystem effects and patients suffering with this ever more prevalent condition present for elective and emergency surgery at all hospitals, not just specialist renal centres. It is therefore important for all surgeons and anaesthetists to be aware of the potential problems associated with the renal dysfunction but also with the underlying cause of the disease. The perioperative management of these patients is complex and requires careful planning to ensure that no acute kidney injury occurs leading to a deterioration in the chronic condition. We summarize the multisystem effects of chronic kidney disease, outline the pre-, peri- and postoperative approach to ensure maintenance of renal blood flow and perfusion pressure and discuss the implications of the disease on drug handling pertinent to the common medications used in the perioperative period including analgesia, anaesthetic agents and antibiotics.